Staying Current: Developing Just-in-time Evidence-Based Learning Objectives for a Maternal Cardiac Arrest Simulation Curriculum - D, Shields Andrea; Jacqueline, Battistelli; Laurie, Kavanagh; Lara, Ouellette; Brook, Thomson; Peter., Nielsen (Cardiology and Cardiovascular Medicine, 2022)
Background: Our objective was to review the latest evidence on resuscitation care for maternal cardiac arrest (MCA) and gain expert consensus on best practices to inform an evidence-based curriculum. Methods: We convened a multidisciplinary panel of stakeholders in MCA to develop an evidence-based simulation training, Obstetric Life SupportTM (OBLS). To inform the learning objectives, we used a novel three-step process to achieve consensus on best practices for maternal resuscitation. First, we reaffirmed the evidence process on an existing MCA guideline using the Appraisal of Guidelines for Research and Evaluation (AGREE II). Next, via systematic review, we evaluated the latest evidence on MCA and identified emerging topics since the publication of the MCA guideline. Finally, we applied a modified Research and Development (RAND) technique to gain consensus on emerging topics to include as additional just-in-time best practices. Results: The AGREE II survey results demonstrated unanimous consensus on reaffirmation of the 2015 American Heart Association (AHA) MCA guideline for inclusion into the OBLS curriculum. A systematic review with deduplication resulted in 11,871 articles for review. After categorizing and synthesizing the relevant literature, we presented twelve additional best practices to the expert panel using a modified RAND technique. Upon completion, the 2015 AHA statement and nine additional just-in-time best practices were affirmed to inform the OBLS curriculum. Conclusions: A novel three-step process including reaffirmation of evidence process, systematic review, and a modified RAND technique resulted in unanimous consensus from experts in MCA resuscitation on existing and new just-in-time best practices to inform the learning ob